Flexible Asymmetric Organic-Inorganic Composite Solid-State Electrolyte Based on PI Membrane for Ambient Temperature Solid-State Lithium Metal Batteries - Yang, Ruilu; Zhang, Zheng; Zhang, Qi; Shi, Jian; Kang, Shusen; Fan, Yanchen (Frontiers in Chemistry, 2022)
Solid-state lithium metal batteries are attracted more and more attention with the developing new energy industry and energy storage industry, because of the high safety and energy density. However, the solid-state electrolytes are usually symmetric and can't be compatible with the cathode and anode at once. In this work, a flexible asymmetric organic-inorganic composite solid-state electrolyte consisting of PI membrane, succinonitrile (SN), LiLaZrTaO(LLZTO), Poly(ethylene glycol) (PEO), and LiTFSi were prepared by solution casting successfully. This lightweight solid electrolyte is stable at the high temperature of 150 ℃ and exhibits a wide electrochemical window of more than 6 V. What’s more, the high ionic conductivity of the flexible solid electrolyte is 7.3×10-7 S/cm. The solid-state batteries assembled with this flexible asymmetric organic-inorganic composite solid electrolyte exhibits excellent performance at ambient temperature. The specific discharge capacity of coin cell using asymmetric organic-inorganic composite solid-state electrolytes is 156.56 mAh/g, 147.25 mAh/g, and 66.55 mAh/g at 0.1C, 0.2C, and 1C at room temperature. After 100 cycles at 0.2C, the reversible discharging capacity is 96.01 mAh/g, and coulombic efficiency is 98%. Considering all the good performance mentioned above, our designed flexible asymmetric organic-inorganic composite solid electrolyte is appropriate for the next-generation solid-state batteries with high cycling stability.